Bezpieczeństwo połączeń w rozległych sieciach komputerowych - Nikodem, Ryszard (Connection Security in Wide Area Networks, 2005)
The article concerns secure connections in VPN (Virtual Private Network). In order to improve network security, protocols such as IPSec and SSL are applied. A network, built from proper components and well managed, is really secure. Other methods, as terminal services and application servers, are also mentioned.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 435-442